Pesantren and Islamic Religious Education (IRE): The Role and Implication of Islamic Boarding School for IRE in Schools - Fauzi, Muhammad Ihsan; Fahrudin, Fahrudin; Abdussalam, Aam (Universitas Pendidikan Indonesia, 2022)
Abstrak. Penelitian ini bertujuan untuk mengetahui penguatan Pendidikan Agama Islam (PAI) melalui pembelajaran kepesantrenan dan mengungkap implikasinya terhadap pembelajaran PAI di sekolah umum. Penelitian ini bersifat kualitatif dengan menggunakan metode deskriptif analitis. Data dalam penelitian ini didapatkan melalui cara : 1) Observasi, 2). Wawancara, 3) Studi dokumen. Hasil penelitian ini meliputi perencanaan penguatan PAI melalui pembelajaran kepesantrenan, proses penguatan PAI melalui pembelajaran kepesantrenan, dan faktor pendukung dan penghambatnya. Adapun implikasi dari penguatan PAI melalui pembelajaran kepesantrenan terhadap pembelajaran PAI di sekolah umum, meliputi implikasi pedagogis teoritis yang mencangkup tujuan, mata pelajaran, sumber, materi, metode, evaluasi, dan pembiasaan. Sedangkan implikasi pedagogis praktis mencankup guru sebagai pendidik dan peserta didik. Kata Kunci: Penguatan PAI, Pembelajaran, Kepesantrenan, PAI di Sekolah Abstract. This study aims to determine the strengthening of Islamic Religious Education (PAI) through Islamic boarding school learning and reveal its implications for Islamic Religious Education learning in public schools. This research is qualitative by using descriptive analytical method. The data in this study were obtained by: 1) observation, 2). Interview, 3) Document study. The results of this study include planning for strengthening PAI through Islamic boarding school learning, the process of strengthening PAI through Islamic boarding school learning, and the supporting and inhibiting factors. As for the implications of strengthening PAI through Islamic boarding school learning of PAI learning in public schools, it includes theoretical pedagogical implications that include objectives, subjects, sources, materials, methods, evaluation, and habituation. Meanwhile, practical pedagogical implications include teachers as educators and students.Keywords: Strengthening PAI, Learning, Islamic Boarding Schools, PAI in Schools